Modulation of thyroid hormone receptors, TR alpha and TR beta, by using different doses of triiodothyronine (T3) at different times - Oliveira, Miriane de [UNESP]; Melo Luvizotto, Renata de Azevedo [UNESP]; Castro Olimpio, Regiane Marques [UNESP]; Sibio, Maria Teresa de [UNESP]; Rodrigues Silva, Carolina Biz; Conde, Sandro Jose [UNESP]; Padovani, Carlos Roberto [UNESP]; Nogueira, Celia Regina [UNESP] (Sbem-soc Brasil Endocrinologia & Metabologia, 2013)
Objective: To examine the effect of different doses of triiodothyronine (T3) on mRNA levels of thyroid hormone receptors, TR alpha and TR beta, at different times. Materials and methods: 3T3-L1 adipocytes were incubated with T3 (physiological dose: F; supraphysiological doses: SI or SII), or without T3 (control, C) for 0.5, 1, 6, or 24h. TR alpha and TR beta mRNA was detected using real-time polymerase chain reaction. Results: F increased TR beta mRNA levels at 0.5h. After 1h, TR alpha levels increased with F and SI and TR beta levels decreased with SII compared with C, F, and SI. After 6h, both genes were suppressed at all concentrations. In 24h, TR alpha and TR beta levels were similar to those of C group. Conclusions: T3 action with F began at 1h for TR alpha and at 0.5h for TR beta. These results suggest the importance of knowing the times and doses that activate T3 receptors in adipocytes.
Modulação dos receptores de hormônio tireoidiano, TRα e TRβ, utilizando diferentes doses de triiodotironina (T3) em diferentes tempos
Keywords: TR alpha; TR beta; triiodothyronine; adipocytes